6a+3b-12a-3b=

Simple and best practice solution for 6a+3b-12a-3b= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6a+3b-12a-3b= equation:


Simplifying
6a + 3b + -12a + -3b = 0

Reorder the terms:
6a + -12a + 3b + -3b = 0

Combine like terms: 6a + -12a = -6a
-6a + 3b + -3b = 0

Combine like terms: 3b + -3b = 0
-6a + 0 = 0
-6a = 0

Solving
-6a = 0

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Divide each side by '-6'.
a = 0

Simplifying
a = 0

See similar equations:

| -0.375-10=20 | | 64x^3-9=0 | | 4(a+9)=44 | | -2(x+6)+10=-96 | | 28=7c-3 | | -4(n+8)= | | (4x-10)(9x-8)= | | 1x+16=8x+56 | | -9/24-10=20 | | x^3-6x^2+0x+20=0 | | 5e-4=31 | | 3x-12+x-4=3 | | -8x+3x+11=46 | | 5+20(x-2)=19 | | 53-4=31 | | 5+20+x=5x+5 | | 4(3s+7)=40 | | 20x-9=2x+9 | | 5e-4=13 | | 5x+5=5+20+0 | | 4(a-4)=68 | | 0=n^2+2n-3 | | 4y-2y+5y= | | (u-3)7=56 | | 8x(x+25)=600 | | 54x^2/27x^3 | | 2x-5=x^2-2x-5 | | 4x-3+0.5x=1.5 | | 7x^2+16-15=0 | | -2(2r-4)=3(r-2) | | 13-6x=29 | | 2x+10+2x=189 |

Equations solver categories